Effectiveness Of Beluntas Leaves (Pluchea indica L.) As A Vegetable Insecticide Against The Mortality Of Gray Worn (Spodoptera litura F) Lepidoptera: Noctuidae - Doga, Ikius; Susanti, Diana Sri; Sembiring, Jefri; Mendes, Johana (Biospecies, 2024)
This study aimed to determine the effectiveness of beluntas leaf extract (Pluchea indica L) as a vegetable insecticide against the mortality of Spodoptera litura pests. This research is experimental consisting of 5 treatments with 1 control and 5 replications in each treatment. Sampling was done by taking 300 larvae of Spodoptera litura instar II that had been reared and propagated in the laboratory. Each treatment was repeated 5 times and each repetition in each treatment was tested as many as 10 larvae of Spodoptera litura instar II. Based on the results of research, beluntas leaf extract (Pluchea indica L.) has a toxic effect on Spodoptera litura insects that have been tested. The highest average number of Spodoptera litura mortality occurred at 90% concentration treatment and beluntas leaf extract (Pluchea indica L.) showed a significant effect on the mortality of Spodoptera litura insects.